Afiks Bahasa Korea dalam Esai Jichyeotgeonna Joahaneun Ge Eopgeona - Adinda Hasna Rahmadia; Usmi Usmi (Universitas Gadjah Mada, 2021)
This study aims to analyze Korean language affixes. The source data in this research was taken from a Korean essay entitled Jichyeotgeona Joahaneun Ge Eopgeona. This study was designed to answer the following research question; how is the classification of affixes contained in the essay Jichyeotgeona Joahaneun Ge Eopgeona based on the theory of affix classification proposed by Kim et al. (2005). This study used mixed methods with descriptive-analytical approach. Based on the results of data analysis, there were found 28 affixes, consisting of 4 prefixes and 24 suffixes in the data source. From the 4 prefixes, it is found that 3 prefixes are attached to the basic form of noun class and 1 prefix is attached to the base form of verb or adjective class. Furthermore, from 24 suffixes, 6 suffixes form verbs, 15 suffixes form nouns, 2 suffixes form adjectives and 1 suffix forms adverbs. Through the results of this study, it is hoped that it will provide readers with additional knowledge and reference materials regarding affixes in Korean.